AL-HAQAIQ AL-IJTIMA’IYAH FI KITAB FIHI MA FIHI LI JALALUDDIN AL-RUMI MIN NADZHARIYAT EMILE DURKHEIM - Muh Khirul Fatihin; Marzuqi Marzuqi; Muhammad Qutbi Hairuddin (Afshaha: Jurnal Bahasa dan Sastra Arab, 2024)
Social can produce forms of reality both consciously and unconsciously. As for Emile Durkheim's view of the concept of social reality is classified into two types, namely material and non-material social reality. The purpose of this study is to represent the forms of social reality contained in the Kitab Fihi Ma Fihi prose by Jalaluddin Al-Rumi. Whether it's material social reality or non-material social reality. This study uses a dialectical mimetic approach, by comparing past and present images in recent studies. The type of research applied is descriptive qualitative.The data used in this study are primary data and secondary data. The primary data in this study is Kitab Fihi Ma Fihi prose. While secondary data is in the form of literature that has relevance to this research, either in the form of articles, books and so on. Data collection techniques were carried out using reading techniques and writing techniques. Furthermore, the last stage in this research is analysis by reduction, presentation and conclusion. The results in this study arethere are several social reality entities in Kitab Fihi Ma Fihi prose. In terms of architecture, such as the "Kaaba", and in terms of technology, such as "astrolabe", then with regard to aspects of social law, there are many laws or standards in war. Including spoils of war, killing and capture. On the aspect of social structure such as leaders and scholars. immaterial social realities such as morality, the collective consciousness of society, collective representation, and collective thinking.